Exploring the Dynamics of Islamization in the Philippines : Past, Present, and Future Perspectives - Guleng, Marlon Pontino; Syaoki, Muhammad; Choirin, Muhammad (Jurnal Dakwah Risalah, 2024)
This study offers a meticulous examination of the past, present, and future trajectories of Islamization in the Philippines, yielding insightful findings that significantly contribute to the scholarly discourse on the topic. By meticulously analyzing historical contexts, socio-political dynamics, and religious influences, alongside employing a rigorous multi-methodological approach encompassing qualitative analysis, quantitative data, fieldwork, archival research, and expert interviews, this study unveils nuanced insights into the complex nature of Islamization processes in the country. The exceptional results of this study not only shed light on key trends, patterns, and drivers shaping Islamization but also provide invaluable guidance for policymakers, stakeholders, and scholars seeking to navigate the evolving landscape of religious dynamics, social cohesion, and national development in the Philippines.